Measurement-induced quantum phases realized in a trapped-ion quantum computer - Noel, Crystal; Niroula, Pradeep; Zhu, Daiwei; Risinger, Andrew; Egan, Laird; Biswas, Debopriyo; Cetina, Marko; Gorshkov, Alexey V.; Gullans, Michael J.; Huse, David A.; Monroe, Christopher (Nature physics, 2022)
Many-body open quantum systems balance internal dynamics against decoherence and measurements induced by interactions with an environment 1 , 2 . Quantum circuits composed of random unitary gates with interspersed projective measurements represent a minimal model to study the balance between unitary dynamics and measurement processes 3 – 5 . As the measurement rate is varied, a purification phase transition is predicted to emerge at a critical point akin to a fault-tolerant threshold 6 . Here we explore this purification transition with random quantum circuits implemented on a trapped-ion quantum computer. We probe the pure phase, where the system is rapidly projected to a pure state conditioned on the measurement outcomes, and the mixed or coding phase, where the initial state becomes partially encoded into a quantum error correcting codespace that keeps the memory of initial conditions for long times 6 , 7 . We find experimental evidence of the two phases and show numerically that, with modest system scaling, critical properties of the transition emerge. Many-body open quantum systems are predicted to undergo a phase transition towards a pure state through frequent projective measurements. The phases separated by this transition have now been observed with random circuits on a trapped-ion computer.